1997
DOI: 10.1046/j.1365-2567.1997.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous killing by a population of intermediate T‐cell receptor cells and its NK1.1+ and NK1.1 subsets, using Fas ligand/Fas molecules

Abstract: SUMMARYSelf-reactive clones, estimated by anti-Vb monoclonal antibodies (mAb) in conjunction with the Mls system, are confined to a population of intermediate (int) T-cell receptor ( TCR) (or CD3) cells (i.e. TCRint cells), but are not found among TCRhigh cells. The next questions to be answered are whether autologous killing is confined to TCRint cells and how such killing is mediated. In this study, 51Cr-labelled thymocytes of syngeneic or allogeneic origin were used as target cells (4-hr assay). When liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
50
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 30 publications
3
50
0
Order By: Relevance
“…In addition to the increase in the total number of lymphocytes at the exposure time of hyperthermia, the number and proportion of CD56 + NK cells, CD57 + NK cells, and CD56 + (or CD57 + ) NKT cells were found to increase. It is known that these NK and NKT cells are associated with immune functions in animals and humans with malignancy (7,13,14,19). It is therefore speculated that the present phenomenon of the immune system might be important for the immunopotentiation of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increase in the total number of lymphocytes at the exposure time of hyperthermia, the number and proportion of CD56 + NK cells, CD57 + NK cells, and CD56 + (or CD57 + ) NKT cells were found to increase. It is known that these NK and NKT cells are associated with immune functions in animals and humans with malignancy (7,13,14,19). It is therefore speculated that the present phenomenon of the immune system might be important for the immunopotentiation of cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, such allogeneic cytotoxicity of liver lymphocytes isolated from mice with PHx was not significantly augmented. In a previous study, 22 we reported that selfreactive cytotoxicity of TCR int cells is mediated by the interaction of TCR on TCR int cells with MHC class I antigens (including CD1 antigen). To this end, we used both class I-deficient and class II-deficient thymocytes.…”
Section: Resistance Of Self-reactive Nkt Cytotoxicity Mediated By Livermentioning
confidence: 96%
“…In contrast to NK cells, TCR int or CD3 int cells have unique cytotoxicity against syngeneic thymocytes (i.e., self-reactive cytotoxicity). 22 In this regard, we examined whether such self-reactive cytotoxicity of liver lymphocytes was suppressed at the early phase (0.5 day) of hepatocyte regeneration (Fig. 7).…”
Section: Resistance Of Self-reactive Nkt Cytotoxicity Mediated By Livermentioning
confidence: 99%
See 1 more Smart Citation
“…In the present case, however, spontaneous regression of the metastatic lesion was observed without any treatment of the primary or metastatic lesions; in addition, there was no infection of the primary or metastatic sites. It was recently reported that immunological mechanisms, including certain cytokines, such as interferon and tumor necrosis factor, may stimulate cytotoxic function against cancer cells, leading to spontaneous regression (17)(18)(19). Unfortunately, blood samples were not obtained for immunological evaluation, as there was no expectation of tumor regression at the time.…”
Section: Discussionmentioning
confidence: 99%